Representaciones imaginarias de la interacción y violencia en la escuela - Villanueva, Concepción Fernández; Castro, Juan Carlos Revilla; Bilbao, Roberto Domínguez; Ferreira Salles, Leila Maria [UNESP]; de Paula e Silva, Joyce Mary Adam [UNESP] (My University, 2011)
School violence research (sociopaedagogical and psychosocial perspectives) has not appropiately taken into account interpersonal and imaginary elements that may be extremely relevant for the understanding of this phenomena. This article analizes the imaginaries that articulates the violence of youth groups in a context of interpersonal relationships in the institutional space of a Rio Claro (Brazil) secondary school. The results are based on the analysis of four youth groups discourses, gathered in succesive group interviews, as well as the drawings made and pictures taken on their respective schools. They show a strong imaginary of generalized violence, in and out the school, with a representation of the school as unfair and aggressor and the students, aggressors themselves, as humiliated and undervalued.
Imaginary representations of interaction: And school violence
Keywords: Brazil; Imaginaries; School violence; Youth